group it.
(2x^3-3x^2) + (2x-3)
= x^2 (2x-3) + (2x-3)
the factors are x^2+1 (2x-3)
2007-10-12 10:10:06
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
2x³ - 3x² + 2x - 3
(2x³ - 3x²) + (2x - 3)
x² (2x - 3) + 1(2x - 3)
(2x - 3) is common
(2x - 3) (x² + 1)
===============
2007-10-12 10:47:10
·
answer #2
·
answered by Joymash 6
·
0⤊
1⤋
2x^3 - 3x^2 + 2x - 3
= x^2(2x-3) +2x-3
= (x^2+1)(2x-3)
2007-10-12 10:09:28
·
answer #3
·
answered by ironduke8159 7
·
0⤊
2⤋
The factor of that would be x
2x^3 - 3x^2 + 2x - 3
or x(2x -3) + (2x -3)
or (x +1)(2x - 3)
or 3x (1x+2x) - 3
= x
2007-10-12 10:08:57
·
answer #4
·
answered by Da1bearsfan 4
·
0⤊
3⤋
I don't need to repeat the answers, but just wanted to caution that the first 4 answers are incorrect, and that you should pay attention to the last three answers before mine, especially that of chrissytimebuds.
It looks complicated at first, but you always want to see where a common factor is, and then use simple math to figure out the cleanest way to express the factors.
good luck
2007-10-12 10:37:31
·
answer #5
·
answered by elecbass100 3
·
1⤊
0⤋
(x^2 + 1)(2x -3)
I basically just fiddled with it until it worked out.
2007-10-12 10:10:26
·
answer #6
·
answered by G.V. 6
·
1⤊
1⤋
2x^3 - 3x^2 + 2x - 3
or x(2x -3) + (2x -3)
or (x +1)(2x - 3)
2007-10-12 10:07:33
·
answer #7
·
answered by ib 4
·
1⤊
2⤋
i think it would be -1x^6+2x-3 so x^6-3 but i'm not sure
2007-10-12 10:07:20
·
answer #8
·
answered by Claire 3
·
0⤊
2⤋
go to tutorials in the morning and you'll find out.
2007-10-12 10:06:14
·
answer #9
·
answered by Anonymous
·
0⤊
2⤋